National partners and champion smallholder farmers in Mali adopt a community-based breeding program for local goats - Tebourbi, Ons; Rekik, Mourad; Getachew, Tesfaye; Haile, Aynalem; Sow, Ahmadou; Zannou, Olivier; Dione, Michel; Marshall, Karen (International Livestock Research Institute, 2024)
o Mali’s first Community-Based Breeding Program (CBBP) for goats was launched in 2023. o Many indigenous breeds are included in the program, namely Djallonké, Bali-Bali, Peulh, and others. o Until now, two CBBPs were established in two villages, namely Siguidolo Wéré and Noukoula in Ségou cercle. The establishment of a third CBBP in Sikasso cercle is now being discussed. o These villages were chosen for their easy accessibility in terms of distance and security, the predominance of goats as livestock species, the presence of typical open-minded breeders focused on production and organized in cooperatives, the availability of input and service suppliers (health, feed, extension, etc.), and the low prevalence of transhumant livestock farming. o In Siguidolo Wéré and Noukoula, a total of 183 households were involved in the CBBP, with a total of 1,237 goats identified. The graphs (Figures 1 and 2) below summarize the details of this output. o Goat selection traits within Mali’s CBBP include fertility, milk yield, growth rate, longevity, adaptability, and resistance to diseases.